The Influence of Leisure Attitudes and Leisure Satisfaction on Adolescents’ Positive Functioning: The Role of Emotion Regulation - Freire, Teresa; Teixeira, Ana (Frontiers in Psychology, 2018)
Scientific research on leisure has proven its contribution to physical and psychological well-being in adolescents, especially regarding the practice of structured leisure activities. Leisure is considered a privileged context for adolescents to develop and learn several developmental skills, such as emotion regulation (ER). Nevertheless, the relationship between leisure and ER has been under-researched in adolescents. The present cross-sectional study aims to test a conceptual model concerning the relationship of leisure attitudes and leisure satisfaction with adolescents’ positive functioning and to explore the role of emotion self-regulation strategies in that relationship. Thus, we hypothesized that leisure attitudes would be a predictor of leisure satisfaction; leisure satisfaction would be a predictor of positive functioning dimensions (self-esteem; satisfaction with life; psychological well-being); and the relationship between leisure satisfaction and positive functioning dimensions would be mediated by emotion self-regulation strategies [cognitive reappraisal (CR) and expressive suppression (ES)]. The participants in this study were 654 adolescents from 10th, 11th, and 12th grade, aged between 14 and 19 years old. Data were collected using self-report questionnaires. The structural equation analysis showed that leisure attitudes are a significant predictor of leisure satisfaction, and that leisure satisfaction significantly predicts all positive functioning dimensions. CR mediated the relationship between leisure satisfaction and self-esteem. These findings highlight the importance of developing positive attitudes toward leisure to increase adolescents’ levels of leisure satisfaction. This study also supports the importance of leisure satisfaction for achieving adolescents’ positive functioning. Future studies should continue to examine the role of emotion self-regulation strategies on leisure, especially regarding CR.